Development of highly potent melanogenesis inhibitor by in vitro, in vivo and computational studies - Abbas, Qamar (Drug Des Devel Ther, 2017)
The present work describes the synthesis of few hydroxylated amide derivatives as melanogenesis inhibitors. In vitro, in vivo and computational studies proved that compound 6d is a highly potent melanogenesis inhibitor compared to standard kojic acid. The title amides 4a–e and 6a–e were synthesized following simple reaction routes with excellent yields. Most of the synthesized compounds exhibited good mushroom tyrosinase inhibitory activity, but compound 6d showed excellent activity (IC(50) 0.15 µM) compared to standard kojic acid (IC(50) 16.69 µM). Lineweaver–Burk plots were used for the determination of kinetic mechanism, and it was found that compounds 4c and 6d showed non-competitive inhibition while 6a and 6b showed mixed-type inhibition. The kinetic mechanism further revealed that compound 6d formed irreversible complex with the target enzyme tyrosinase. The Ki values determined for compounds 4c, 6a, 6b and 6d are 0.188, 0.84, 2.20 and 0.217 µM respectively. Results of human tyrosinase inhibitory activity in A375 human melanoma cells showed that compound 6d exhibited 91.9% inhibi-tory activity at a concentration of 50 µg/mL. In vivo cytotoxicity evaluation of compound 6d in zebrafish embryos showed that it is non-toxic to zebrafish. Melanin depigmentation assay performed in zebrafish indicated that compound 6d possessed greater potential in decreasing melanin contents compared to kojic acid at the same concentration. Computational studies also supported the wet lab findings as compound 6d showed a highest binding affinity with the target protein (PDBID: 2Y9X) with a binding energy value of −7.90 kcal/mol. Molecular dynamic simulation studies also proved that amide 6d formed the most stable complex with tyrosinase. Based upon our in vitro, in vivo and computational studies, we propose that compound 6d is a promising candidate for the development of safe cosmetic agent.